Leveraging microbial biosynthetic pathways for the generation of 'drop-in' biofuels. (June 2017) - Zargar, Amin; Bailey, Constance B; Haushalter, Robert W; Eiben, Christopher B; Katz, Leonard; Keasling, Jay D
Graphical abstract: Highlights: Fatty acid, isoprenoid and polyketide pathways for production of drop-in biofuels. FAS pathways produce alkanes via newly discovered fatty aldehyde decarbonylase. Crystallized geranylgeranyl reductase hydrogenates isoprenoid-based double bonds. Polyketide synthases for generation of designer biofuels. Abstract : Advances in retooling microorganisms have enabled bioproduction of 'drop-in' biofuels, fuels that are compatible with existing spark-ignition, compression-ignition, and gas-turbine engines. As the majority of petroleum consumption in the United States consists of gasoline (47%), diesel fuel and heating oil (21%), and jet fuel (8%), 'drop-in' biofuels that replace these petrochemical sources are particularly attractive. In this review, we discuss the application of aldehyde decarbonylases to produce gasoline substitutes from fatty acid products, a recently crystallized reductase that could hydrogenate jet fuel precursors from terpene synthases, and the exquisite control of polyketide synthases to produce biofuels with desired physical properties ( e.g., lower freezing points). With our increased understanding of biosynthetic logic of metabolic pathways, we discuss the unique advantages of fatty acid, terpene, and polyketide synthases for the production of bio-based gasoline, diesel and jet fuel.